CITIZENS AND INSTITUTIONS BETWEEN COMPUTERS AND INTERNET - AN EMPYRICAL EVIDENCE FROM THE ITALIAN CASE - Carlo Tesauro (European Regional Science Association (ERSA), 2005)
The diffusion of ICT technologies that generated the Internet phenomenon, is responsible of the world-wide incredible expectation level related to its high potential contribution to problem solution in many socio-economic sectors. In facts, the contribution of ICT in some sectors, as organizations management (public or private, profit or no-profit), was undoubtedly highly effective. The interaction between citizens and institutions is also considered extremely interesting, as the specific funds appropriation since the end of 90es of European Union on these topics can demonstrate. This wide interest caused the expectation of a remarkable services improvement, but the obtained results doesn't seem as much satisfactory. This international and European scenario had a meaningful reflex also in Italian case, because the lack of information flows between Institutions and citizens in our country is always strongly perceived as critical point. In a former study of 1998 (Tesauro, Campisi), some institutional web sites was included in a wider study sample about the usage of internet communications, reaching unflattering results. Nevertheless, some recent "accidents” in citizen-institution relationships, widely reported by mass media and strictly related to computer technologies, suggest remarkable doubts about the usage of these technologies. This happen in spite of the creation of a specific Ministry in Italy and five years later the cited study, an incredible amount of time in terms of evolutionary dynamic of virtual environment). So, the main objective of this contribution is to show a scenario of citizen-institution relation via Internet in Italy at different scales (national, regional and local), identifying strength or weak points not only from users viewpoint and trying to underline the difficulties inherited from a poor usage of actual computer knowledge.
Keywords: 330